THE INTERSECTION OF SUSTAINABILITY AND DIGITAL TRANSFORMATION IN THE BUSINESS TOURISM INDUSTRY (International Congress on Economics, Management and Business Studies, 2026)
This article examines how sustainability and digital transformation converge to reshape the business tourism industry. Drawing on verified data from the World Economic Forum, WTTC, Bain & Company, UN Tourism, Grand View Research, and the Net Zero Carbon Events initiative, the study analyzes five domains where sustainability and digitalization intersect: hybrid event formats, smart destination management, AI-driven resource optimization, carbon measurement technologies, and digital sustainability communication. The global travel and tourism sector contributed $11.1 trillion to the world economy in 2024 (WTTC), while the MICE market reached approximately $946 billion in 2025, with over 35% of corporate clients now requiring green travel compliance. The article proposes an integrated framework for sustainable digital business tourism and discusses implications for emerging destinations.
Keywords: Sustainability, digital transformation, business tourism, MICE, hybrid events, carbon neutrality, smart destinations, green tourism, AI in tourism, Net Zero Carbon Events.